Digital-Twin-Based Evaluation of Nearly Zero-Energy Building for Existing Buildings Based on Scan-to-BIM - Liang Zhao; Hong Zhang; Qian Wang; Haining Wang (Advances in Civil Engineering)
In recent years, the global energy environment has become increasingly severe, and the problems such as global warming, soaring carbon emissions, and excessive use of petrochemical energy have attracted increasing attention from all walks of life. The construction industry, which accounts for about 30% of the total energy consumption, needs to effectively manage and use renewable energy. The application of building information model (BIM) in the evaluation of retrofitting schemes of existing buildings is one of the main research issues in the field of building digital twins at present. The method of this research is to use 3D laser scanning technology to efficiently create the building energy model (BEM) of existing buildings and to identify and evaluate the feasibility of existing building retrofitting schemes. The purpose of this research is to evaluate the retrofitting scheme of existing buildings based on the concept of nearly zero-energy buildings (nZEBs), aiming to improve the energy efficiency of existing buildings and use clean energy to satisfy building energy demand. According to the case study in this paper, an nZEBs solution suitable for the building can reduce building energy costs by 14.1%, increase solar photovoltaic power generation by 24.13%, and reduce carbon dioxide emissions by 4306.0 kg CO2eq/a.